The Labor Market in the Netherlands 2001–2024: The Long Demise of a Centralized Model - Wiemer Salverda; Joop Hartog (Institute of Labor Economics (IZA), 2025)
The Netherlands has long been an example of a highly and centrally institutionalized labor market paying considerable attention to equity concerns. We describe how this model has been falling apart under the influence of the neoliberal ideology. Fracturing of the labor force by the rapid demise of the single-earner model and accelerating immigration, falling union density, and reductions in welfare state provisions have shrunk labor's market power centrally and decentrally. Wages lagged far behind productivity growth, job security strongly declined and wage inequality increased. This comes to the fore with a lack of offensive union power when after 2016 labor demand accelerates and the economy and employment quickly reach new heights after the pandemic crisis.
Keywords: J21; J31; J61; 330; wages; institutions; dual earners; Netherlands